(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Adding 5% hydrogen to a conventional gasoline-air mixture in a gasoline engine reduced the effective fuel consumption by 14% and the amount of unburned hydrocarbons in the exhaust gases by 2-3 times, and carbon monoxide by 0.1%. The addition of hydrogen increased the octane number of gasolines to 8-10 units and completely eliminated the use of tetraethyl lead added to them